A Mid-Term Evaluation of Vietnamese Energy Policy for the Greenhouse Gas Reduction Using Dynamic GTAP-E Model - DO DINH LONG (The Graduate School, Ajou University, 2012)
In the last ten years, several emerging countries including Vietnam have experienced dramatic economic growth rate. As a result, energy demand in these economies has been increasing rapidly, which leads to the concern of climate change and the shortage of energy resources. In this context, energy system analysis has become an urgent issue due to the growing concerns related to climate change, land use, differentiation of energy sources and energy prices. The analysis of the impacts between international trade and climate change suggests the use of global model type for climate change policy evaluation. Since the global economy includes the complex interrelationships between trade, economic activities and climate change, Computable General Equilibrium (CGE) model is considered to be an appropriate tool for energy policy analysis due to its advantages. One of the Computable General Equilibrium (CGE) models known as The Global Trade Analysis Project (GTAP) is a global project aiming at facilitating high quality quantitative analysis of the global economic issues. The main products of the GTAP are the global database (the GTAP Data Base) and the global economic model (the standard GTAP model) to conduct policy simulations with the GTAP Data Base. The standard GTAP model is a comparative static multi-regional CGE model of the world economy written in the GEMPACK software that was developed by the Centre of Policy Studies, MONASH University. The GTAP-E model is an extension of the standard GTAP model constructed by the Global Trade Analysis Project (GTAP) team. The model incorporates energy substitution both for inter-fuel and fuel-factor substitution into the Standard GTAP model. This new features allow the estimation of sectoral energy consumptions by fuel type - one important step to estimate carbon emission from fuel combustion. The model assumes that capital and energy composite are substitutable to a certain extent and form capital – energy composite. Different types of energy are nested at several levels based on their substitutability. Aside from energy substitution modules, several other modules are also presented. Since the development of the original GTAP-E model, there are number of studies utilized the structure of this model and the revised version for policy analysis of climate change. However, literature survey shows that there is no application using dynamic GTAP-E for the evaluation of the impacts of carbon tax. Moreover, it also indicates the lack of GTAP-E application for the examination of carbon tax adoption for Vietnam. For the last two decades, Vietnam has emerged as one the most active economy in the world. Rapid energy demand with low energy efficiency leads to high growth rate of greenhouse gases emission. As a result, environmental problems should be considered and policy to mitigate the negative impact of greenhouse gases, especially CO2 ¬emission should be carefully examined. In order to contribute to that process, the application of GTAP-E model for simulating the adoption of carbon tax for the case of Vietnam is carried out in this study. The first stage is the application of a static GTAP-E model. Steps in the process of building the GTAP-E model for Vietnam are identified as follows: specifying the model to be used, choosing regional and sectoral aggregation, preparation of technical files for the model to be run, and final step is the preparation of parameters and data which comprises of economic data, energy and CO2 emission data. The results of simulation under three scenarios of carbon taxation for Vietnam show that carbon taxation reduces CO2 emission as expected. Moreover, results of other regions in the model show consistent meanings for the adoption of carbon tax. However, the adoption of carbon tax also causes problem for energy sector and the national economy such as the increase of energy prices and contraction of industry output which in turn affects the industry competitiveness and leads to GDP reduction. Finally, it can be observed that impacts seem to be relatively greater when carbon tax set at smaller level. As the second step, the static GTAP-E model is extended to a dynamic version by solving a series of static equilibria driven by the evolvement of some key exogenous variables such as GDP, population, skilled and unskilled labor. The results show that the implementation of carbon tax of 20 US dollars per ton of carbon increasingly reduces CO2 emission reduction in the future while having little impacts on GDP. Although the results of dynamic GTAP-E model for Vietnam suggest the implementation of carbon tax in the future, the discussion also implies that the adoption of carbon taxation for Vietnam should be further examined and evaluated. This is because there are several ways of reducing CO¬2 emissions which need to be compared or need to be combined together so that the adoption of energy policy will come at a reasonable economic cost. The application of GTAP-E model for Vietnam in this research would be the first energy policy evaluation for Vietnam using a global model. One problem for global model is the collection of the data, either baseline data for dynamic model or energy data for energy-environmental analysis. With the data collected for this study, the application of the GTAP-E model and dynamic GTAP model for Vietnam can be replicated for any other country and region presented in the GTAP version 7 data base as long as energy data and CO2 emission data are available for that country or region.
아주대학교 일반대학원 :에너지시스템학부,2012. 2